Performance Appraisal System at Bayukarta Hospital - Damanik, Santy Afriaty; Suroso, Suroso; Anggela, Flora Patricia (Jurnal Ilmiah Sumber Daya Manusia, 2022)
This study aims to find out how the job appraisal system at Bayukarta Hospital is, the job appraisal procedure, the assessment points used in the assessment and the obstacles. This research uses descriptive writing method. Based on our research, it can be concluded that the work appraisal system at the Bayukarta Hospital has been running smoothly and well, although it is still considered to be less transparent, but in carrying out the company's employee appraisal policy, it can handle it well.